Increased Susceptibility of Mice Lacking Renin-b to Angiotensin II–Induced Organ Damage. Issue 2 (August 2020) - Nakagawa, Pablo; Nair, Anand R.; Agbor, Larry N.; Gomez, Javier; Wu, Jing; Zhang, Shao Yang; Lu, Ko-Ting; Morgan, Donald A.; Rahmouni, Kamal; Grobe, Justin L.; Sigmund, Curt D.
Abstract : Several cardiac and renal diseases are attributed to a dysregulation of the renin-angiotensin system. Renin, the rate-limiting enzyme of the renin-angiotensin system, has 2 isoforms. The classical renin isoform (renin-a) encoding preprorenin is mainly confined to the juxtaglomerular cells and released into the circulation upon stimulation. Alternatively, renin-b is predicted to remain intracellular and is expressed in the brain, heart, and adrenal gland. In the brain, ablation of renin-b (Ren-b Null mice) results in increased brain renin-angiotensin system activity. However, the consequences of renin-b ablation in tissues outside the brain remain unknown. Therefore, we hypothesized that renin-b protects from hypertensive cardiac and renal end-organ damage in mice. Ren-b Null mice exhibited normal blood pressure at baseline. Thus, we induced hypertension by using a slow pressor dose of Ang II (angiotensin II). Ang II increased blood pressure in both wild type and Ren-b Null to the same degree. Although the blood pressure between Ren-b Null and wild-type mice was elevated equally, 4-week infusion of Ang II resulted in exacerbated cardiac remodeling in Ren-b Null mice compared with wild type. Ren-b Null mice also exhibited a modest increase in renal glomerular matrix deposition, elevated plasma aldosterone, and a modestly enhanced dipsogenic response to Ang II. Interestingly, ablation of renin-b strongly suppressed plasma renin, but renal cortical renin mRNA was preserved. Altogether, these data indicate that renin-b might play a protective role in the heart, and thus renin-b could be a potential target to treat hypertensive heart disease. Abstract : Supplemental Digital Content is available in the text.